The teachers’ self-efficacy and its importance for inclusive education - NARKUN, ZUZANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Zuzanna Narkun, The teachers’ self-efficacy and its im-portance for inclusive education. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 151-176. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https:// doi.org/10.14746/ikps.2019.25.07 The aim of this article was to describe the teachers’ self-efficacy, self-efficacy for the purpose of inclusive practices, and to show its importance for the development of inclusion. Issues related to the self-efficacy of teachers (the definitions, the sources of self-efficacy, and the measurement of teachers’ self-efficacy) have been described. The resulting findings of the research on teachers’ self-efficacy, its antecedents and consequences have been presented. Moreover, connections between self-efficacy and effective implementation of inclusion have been discussed.